Model for Cell Wall Growth of Streptococcus faecalis - Higgins, Michael L. (1970)
In exponentially growing and dividing cells of Streptococcus faecalis, it is proposed that the leading edge of the annularly closing cross wall is the point of extension for both cross wall and peripheral wall. Peripheral wall extension is thought to be produced by the separation or splitting of the cross wall at its junction with peripheral wall. This results in the pushing of the equatorial wall bands, found on S. faecalis walls, to subsequatorial positions. These bands therefore mark the separation of old wall from new wall. Mesosomal formation was observed usually to precede cross wall initiation.